The Effects Of Social Media Content, Influencer Marketing And Customer Reviews On Purchasing Decisions - Setia Pratama, Ade; Ilham, Rachmad; Sutomo, Sutomo; Hermawan, Agus; Wisnu Wardhana, Ludi (International Journal of Science, Technology & Management, 2024)
This research aims to determine the effect of social media content, influencer marketing , and customer reviews on purchasing decisions on Shopee online marketing platform during period January-March 2024. The independent variables in this research are social media content, influencer marketing , and customer reviews , while the dependent variable is purchasing decisions. This research uses primary data in the form of questionnaire results from respondents. This research uses a purposive sampling technique . The method used is a type of quantitative research . The analysis used in this research is multiple linear analysis. In this research, it shows that social media content has significance effect on purchasing decisions, influencer marketing has no effect on purchasing decisions, customer reviews has no effect on purchasing decisions but the variables social media content (X1), influencer marketing (X2) and customer reviews (X3) simultaneous influence on purchasing decisions (Y) with a significance value (Sig) of 0.000 < 0.05.